2001
DOI: 10.1007/s004060170039
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of alcohol withdrawal: tiapride and carbamazepine versus clomethiazole.

Abstract: In Germany, clomethiazole (CLO) and benzodiazepines are predominantly used as therapeutic agents in the treatment of the alcohol withdrawal syndrome (AWS). These agents have disadvantages such as sedation, risk of respiratory insufficiency, and cardiovascular complications as well as addictive potential. Alternatively, it could be demonstrated that both tiapride (TIA) and carbamazepine (CBZ) are efficient in the treatment of AWS with less toxicity. However, they seem to be less effective in AWS than CLO as sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 16 publications
1
30
1
5
Order By: Relevance
“…The administration of both clomethiazole and benzodiazepines must be short-term, with gradual dose reduction after a steady state is achieved; in benzodiazepines, approximately to 15-20% of the total dose a day 36 . Some studies comparing clomethiazole with benzodiazepines showed its effectiveness and some of them reported shortening and generally better tolerance of treatment as well 69,86,87 .…”
Section: Clomethiazolementioning
confidence: 99%
See 2 more Smart Citations
“…The administration of both clomethiazole and benzodiazepines must be short-term, with gradual dose reduction after a steady state is achieved; in benzodiazepines, approximately to 15-20% of the total dose a day 36 . Some studies comparing clomethiazole with benzodiazepines showed its effectiveness and some of them reported shortening and generally better tolerance of treatment as well 69,86,87 .…”
Section: Clomethiazolementioning
confidence: 99%
“…The anticonvulsants of non-benzodiazepine type carbamazepine and oxcarbazepine with likely GABA-ergic and NMDA-blocking activity represent other drugs of possible use 87,95,96 . Carbamazepine has been used for over 30 years to treat alcohol withdrawal as a non-addictive, nonsedating agent reducing alcohol withdrawal symptoms 52,87 .…”
Section: Antiepilepticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its inhibitory effects are exerted by postsynaptic receptors that are coupled directly to anion channels (GABA A ) and also by presynaptic G-protein coupled receptors (GABA B ). Extracellular recordings of cultured animal neurons have shown that CMZ is capable of potentiating the inhibitory effects of GABA and muscimol (a specific GABA A agonist) (9). CMZ does not alter levels of inhibitory neuropeptide within the brain but can modulate its actions.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Desde el punto de vista del tratamien-to del SAA presenta los siguientes efectos terapéuti-cos: ansiolisis a través de mecanismo desconocido, alivia el sufrimiento psíquico, disminuye trastornos del sistema nervioso autónomo así como el insomnio; asimismo, mejora la abstinencia alcohólica (65) . En un estudio piloto reciente se muestra que aunque tiapride por sí solo no sea tan eficaz como clometiazol, sin embargo en combinación con carbamacepina es igualmente eficaz e incluso superior en el tratamiento de síntomas vegetativos (66) .…”
Section: Tratamiento Farmacológico Del Síndrome De Abstinencia Alcohóunclassified